Technologies and Means of Processing Graphic Information - Botirovich, Khayriddinov Shavkat (International Journal on Orange Technologies, 2023)
The spread of computer graphics began with printing. But soon she escaped from the cramped premises of printing houses into the scope of wide application. Computer games, scientific graphics and films have gained immense popularity. This article provides information on graphic data processing technologies and tools.